Inspiração em cenas e atos: pesquisa com crianças para a formação de coordenadores - Arantes, Priscila Barbosa (2018)
This research brings a possibility of formation to Pedagogical Coordinators, among active and direct participation of children, bring them like subjects and social actors in the research process by itself. It´s an investigation that purposes new perspectives of listening and looking in relation to children, once brings two central concepts of a new Childhood Sociology: children like social agent, active and creative and childhood like a structural way, like a part of society since birth. This observation purposed is by the owner figure of Coordinator, which put himself like a researcher adult who comes to children field and will participate just if been accepted by this group. There are no artificial purposes by the researcher, but an observation about routines and records. Thus, there is no structural questions beforehand, because relation will be done by enter, acception and participation of researcher, that will show us a view of production and reproduction culture process. Converges on current requests of Chilhood Sociology, for bring a cooperation view, that puts children as subject as the researcher, forming studies with and not about childhood. Children interact in the world because product their own cultures: enter by their families, but product and participate of a lot of peer cultures. Researches that defend listening and focus childhood and children culture consider children point of view in researches. It´s a kind of repair for long time that children were marginalized, in Sociology and other areas, and occupied a subordinated position in society. Besides to suggest a formation with active participation of children this project purposes to enlarge peer culture concept, looking for production of culture actions and analyze interpretative reproduction between children. This purpose converges on listening defense and childhood and children culture focus, under a newer technology and challenger, which involves a detachable view from adult’s point of view